2014
DOI: 10.1186/s12879-014-0703-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosisUganda II family and resistance to first-line anti-tuberculosis drugs in Uganda

Abstract: BackgroundThe global increase in the burden of multidrug-resistant tuberculosis (MDR-TB) underscores an urgent need for data on factors involved in generation and spread of TB drug resistance. We performed molecular analyses on a representative sample of Mycobacterium tuberculosis (MTB) isolates. Basing on findings of the molecular epidemiological study in Kampala, we hypothesized that the predominant MTB strain lineage in Uganda is negatively associated with anti-TB drug resistance and we set out to test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The prevelance of rifampicin resistance non-Beijing families were less than 6% and were found in all WHO Regions. For instance, resistance Haarlem family was reported from Region of American, South-East Asia and European Region [17, 23, 28], CAS reported from South-East Asia, European and African Region and EAI and T families were reported from Western Pacific, South-East Asia, European and African Region [25, 29, 33, 39]. Ural was the only strain reported from East Medterranian Region, in Iran as rifampicin resistance, but it was identfed in South-East Asia, India and Region of American, Brazil, with low prevelance [15].…”
Section: Resultsmentioning
confidence: 99%
“…The prevelance of rifampicin resistance non-Beijing families were less than 6% and were found in all WHO Regions. For instance, resistance Haarlem family was reported from Region of American, South-East Asia and European Region [17, 23, 28], CAS reported from South-East Asia, European and African Region and EAI and T families were reported from Western Pacific, South-East Asia, European and African Region [25, 29, 33, 39]. Ural was the only strain reported from East Medterranian Region, in Iran as rifampicin resistance, but it was identfed in South-East Asia, India and Region of American, Brazil, with low prevelance [15].…”
Section: Resultsmentioning
confidence: 99%
“…tuberculosis sub-lineage Uganda strains that are predominant in Uganda explains the previously reported weak association between MDR-TB and M . tuberculosis Uganda genotype [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated drug-resistance and virulence as factors associated with the predominance of the M. tuberculosis Uganda family in Uganda. In one of the studies, we found that the M. tuberculosis Uganda family is three times less likely to be resistant to first-line anti-TB drugs and five times less likely to be multidrug resistant, compared to the non-Uganda II families [ 5 ]. Furthermore, in the other study investigating virulence we found that the M. tuberculosis Uganda family was less virulent as defined by cavitary disease [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis Uganda is a sub-lineage of the M. tuberculosis lineage 4, the Euro- American lineage which is defined by RD 724 deletion [ 4 – 8 ]. The M. tuberculosis Uganda family comprises M. tuberculosis Uganda I and Uganda II subfamilies with the latter being more prevalent in Uganda [ 5 , 7 ]. Asiimwe et al, 2008 [ 4 ], Nabyonga et al, 2011 [ 7 ], and more recently Ezati et al, 2014 [ 5 ], reported higher occurrence in Uganda of the M. tuberculosis Uganda subfamily (>70 %) compared with other genotypes combined (LAM, Delhi/CAS and Beijing families about 3 % each).…”
Section: Introductionmentioning
confidence: 99%